Raising the Quality of Spesialists’ Training: the Procedure Selection - M. N. Oskina (Образование и наука)
At the time of educational system reorganization, the higher school’s fast response to the changing personal, labor market and society demands becomes even more relevant. The content flexibility of educationalcurricula and graduates’ qualification are regarded as the main criteria for the budget funding of a particular educational institution. The paper considers the ways for overcoming the Russian higher school’s problems, and improving the competitiveness and education quality assurance. As a solution, the author puts forward the priority selection aimed at improving the education quality in a particular institution and university complex. The above algorithm involves the two following stages: first, the necessary activities are rated according to their prospective impact; then the selected list of actions and implementation sequences are specified considering the maximum productivity of the resources and efforts applied. The author recommends the expert assessment method for conducting the first stage procedure, and Pareto method for the last one. The application of the priority selection algorithm is exemplified by the procedures conducted in Ural State University of Railway Transport. The research data can be of interest to the heads of educational institutions and university complexes.